Peningkatan Keterampilan Guru Dalam Penerapan Metode Pembelajaran Inovatif Melalui Kegiatan Pembinaan Berkelanjutan Di SDN 014 Tanjung Selor - Samuel, Samuel (Universitas Cokroaminoto Yogyakarta, 2023)
This School Action Research (PTS) aims to improve teacher skills in applying innovative learning models through ongoing coaching activities. The research subjects were 9 teachers at SDN 014 Tanjung Selor. Data collection techniques used are observation and documentation. Analysis with triangulation technique. Based on the results of the study it can be concluded that there was an increase in teacher skills from the initial conditions as many as 8 teachers were declared not to have skills in applying good innovative learning methods or 0% with an average rating of 48.67, increasing to 4 teachers or 44.44% in the first cycle with an average value of 68.84 and 100% in the second cycle with an average value of 88.80. The explanation of the value criteria from the initial conditions was LESS, increased to ENOUGH and GOOD in the last cycle.